Applications of differential equations in engineering and mechanics - Chau, K. T. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This second of two comprehensive reference texts on differential equations continues coverage of the essential material students they are likely to encounter in solving engineering and mechanics problems across the field - alongside a preliminary volume on theory. This book covers a very broad range of problems, including beams and columns, plates, shells, structural dynamics, catenary and cable suspension bridge, nonlinear buckling, transports and waves in fluids, geophysical fluid flows, nonlinear waves and solitons, Maxwell equations, Schrodinger equations, celestial mechanics and fracture mechanics and dynamics. The focus is on the mathematical technique for solving the differential equations involved. All readers who are concerned with and interested in engineering mechanics problems, climate change, and nanotechnology will find topics covered in this book providing valuable information and mathematics background for their multi-disciplinary research and education.
OCLC-licensed vendor bibliographic record.
Keywords: Engineering mathematics; Differential equations; TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference